Theranostic AGuIX nanoparticles as radiosensitizer: A phase I, dose-escalation study in patients with multiple brain metastases (NANO-RAD trial). (July 2021) - Verry, Camille; Dufort, Sandrine; Villa, Julie; Gavard, Marylaure; Iriart, Carole; Grand, Sylvie; Charles, Julie; Chovelon, Benoit; Cracowski, Jean-Luc; Quesada, Jean-Louis; Mendoza, Christophe; Sancey, Lucie; et al.
Highlights: Administration of theranostics AGuIX nanoparticles is safe and feasible in patients with brain metastases. Brain metastases are detected by MRI up to 1 week after administration of theranostics nanoparticles. Tumor responses correlate with the concentration of theranostics nanoparticles in the metastases assessed by MRI. All but one patient experienced stabilization or decrease in tumor volume. Abstract: Background and purpose: Brain metastasis impacts greatly on patients' quality of life and survival. The phase I NANO-RAD trial assessed the safety and maximum tolerated dose of systemic administration of a novel gadolinium-based nanoparticle, AGuIX, in combination with whole brain radiotherapy in patients with multiple brain metastases not suitable for stereotactic radiotherapy. Materials and methods: Patients with measurable brain metastases received escalating doses of AGuIX nanoparticles (15, 30, 50, 75, or 100 mg/kg intravenously) on the day of initiation of WBRT (30 Gy in 10 fractions) in 5 cohorts of 3 patients each. Toxicity was assessed using NCI Common Terminology Criteria for Adverse Events v4.03. Results: Fifteen patients with 354 metastases were included. No dose-limiting toxic effects were observed up to AGuIX 100 mg/kg. Plasma elimination half-life of AGuIX was similar for all groups (mean 1.3 h; range 0.8–3 h). Efficient targeting of metastases (T1 MRI enhancement, tumor selectivity) and persistence of AGuIX contrast enhancement were observed in metastases from patients with primary melanoma, lung, breast, and colon cancers. The concentration of AGuIX in metastases after administration was proportional to the injected dose. Thirteen of 14 evaluable patients had a clinical benefit, with either stabilization or reduction of tumor volume. MRI analysis showed significant correlation between contrast enhancement and tumor response, thus supporting a radiosensitizing effect. Conclusion: Combining AGuIX with radiotherapy for patients with brain metastases is safe and feasible. AGuIX specifically targets brain metastases and is retained within tumors for up to 1 week; ongoing phase II studies will more definitively assess efficacy.